2019
DOI: 10.1155/2019/3658507
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Corrosion Resistance of Recycled Aluminum Alloy 6061 Chips Using Hot Extrusion Followed by ECAP

Abstract: The oxidation of aluminum machining chips retards the successful recycling through the conventional remelting route. A promising approach to overthrow this problem is the utilization of solid state recycling in converting aluminum machining chips directly into semifinished products to eliminate the cost of the remelting process and reduce CO2 emissions. Therefore, in recent work, chips of aluminum alloy (AA6061) were recycled by compaction and then extrusion conducted at 500°C, followed by equal channel pressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Haase et al [261] recycled machined AA6060 aluminum alloy chips using hot extrusion and subsequent cold extrusion. Taha et al [262] recycled AA6061 aluminum alloy chips using the hot extrusion process followed by equal channel angular pressing (ECAP) and observed enhancement in corrosion resistance of the material. Selmy et al [263] recycled AA6061 aluminum alloy chips using hot extrusion process followed by ECAP.…”
Section: Hot Extrusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haase et al [261] recycled machined AA6060 aluminum alloy chips using hot extrusion and subsequent cold extrusion. Taha et al [262] recycled AA6061 aluminum alloy chips using the hot extrusion process followed by equal channel angular pressing (ECAP) and observed enhancement in corrosion resistance of the material. Selmy et al [263] recycled AA6061 aluminum alloy chips using hot extrusion process followed by ECAP.…”
Section: Hot Extrusionmentioning
confidence: 99%
“…Aluminum alloys [260][261][262][263][264][265]267], bronze [266], reinforced magnesium matrix composite [275].…”
Section: Hot Extrusion Direct Conversionmentioning
confidence: 99%
“…Solid recycled specimens exhibited an excellent combination of high strength and high elongation to failure at room temperature, which was attributed to the refined microstructure, but lower corrosion properties, attributed to the excessive iron contamination that promoted galvanic corrosion [25]. Several researchers have investigated the influence of ECAP on the corrosion properties of aluminium alloys [26][27][28][29][30][31]. They found that the ECAP processing facilitated passivation, increased the thickness of the oxide layer, and the decreased corrosion rate, which was attributed to the significantly reduced grain size in solid recycled specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, Kadir et al [23] applied hot compact (homogenization) to AA6061 recycled aluminum alloy chip and aluminum powder samples prior to extrusion at different preheating temperature periods extending from twenty minutes to six hours. AA6061 alloy chips were recycled by Taha et al, [24]. Using a die with a 90° angle.…”
Section: Introductionmentioning
confidence: 99%